2004
DOI: 10.1037/0893-3200.18.2.372
|View full text |Cite
|
Sign up to set email alerts
|

Marital Violence, Co-Parenting, and Family-Level Processes in Relation to Children's Adjustment.

Abstract: A multimethod approach was used to examine relations between marital violence, coparenting, and family-level processes and children's adjustment in a community-based sample of marital violence. Two hypotheses were tested, one in which family-level and co-parenting processes mediate relations between marital violence and child functioning and one in which marital violence and family-level/co-parenting processes function relatively independently in influencing children's adjustment. Observations of family proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
1
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 39 publications
8
105
1
10
Order By: Relevance
“…This is an important realization for the field of research on family processes in relation to children's effortful control. Associations between coparenting and children's adjustment have been found in previous studies (Katz & Low, 2004;McHale & Rasmussen, 1998;Schoppe et al, 2001). Few studies, however, have examined relations between coparenting and temperamental factors that are assumed to underlie this adjustment (Belsky et al, 1996;McHale et al, 1996;Stright & Bales, 2003), and even fewer studies have examined these relations after accounting for individual parenting (Belsky et al, 1996;McHale et al, 1996).…”
Section: Table 3 Contribution Of Observed Parenting and Coparenting Tmentioning
confidence: 74%
See 1 more Smart Citation
“…This is an important realization for the field of research on family processes in relation to children's effortful control. Associations between coparenting and children's adjustment have been found in previous studies (Katz & Low, 2004;McHale & Rasmussen, 1998;Schoppe et al, 2001). Few studies, however, have examined relations between coparenting and temperamental factors that are assumed to underlie this adjustment (Belsky et al, 1996;McHale et al, 1996;Stright & Bales, 2003), and even fewer studies have examined these relations after accounting for individual parenting (Belsky et al, 1996;McHale et al, 1996).…”
Section: Table 3 Contribution Of Observed Parenting and Coparenting Tmentioning
confidence: 74%
“…Coparenting includes supportive and hostile-competitive dimensions, as well as discrepancies between partners in parent-child warmth and investment (McHale, 1997;Schoppe, Mangelsdorf, & Frosch, 2001). High levels of undermining coparenting (e.g., hostility-competitiveness, child-rearing disagreements) and low levels of supportive coparenting (e.g., family harmony) have been found to be associated with behavioral problems and peer relationships in preschoolers (Katz & Low, 2004;McHale & Rasmussen, 1998;Schoppe et al, 2001).…”
mentioning
confidence: 99%
“…Sexo (1 «varón»; 0 «mujer»); I = Inconsistencia (1 «inconsistencia», 0 «consistencia»). β= coeficientes estandarizados consistencia interparental y la aparición tanto de manifestaciones interiorizadas, tales como la ansiedad y la depresión (Buchanan et al, 1996;Katz y Low, 2004) como exteriorizadas, tales como la agresión (Block et al, 1981;McHale y Rasmussen, 1998;Vaugh et al, 1988), dan apoyo a los presentes resultados. Particularmente, la inconsistencia en el control parental se ha asociado reiteradamente con las manifestaciones exteriorizadas en los hijos (Pettit y Laird, 2002;Pettit, Laird, Dodge, Bates, y Criss, 2001).…”
Section: Discussionunclassified
“…In a study involving families with preschoolage children, Katz and Low (2004) found that marital conflict and violence were associated with less supportive and less positive parenting behaviors. also found an association between marital dysfunction and hostile parenting behavior.…”
Section: Marital Subsystemmentioning
confidence: 99%